The Effect of Nurse-Led Diet and Physical Activity Program for Health on Diet and Physical Activity Behavior of Children - ERGÜN, AYŞE (HUMAN KINETICS PUBL INC, 2019)
Background: Many health problems encountered in childhood, adolescence, and adulthood periods arise from problematic eating behavior, an unhealthy dietary approach, and inactive lifestyles. The aim of this study was to determine the effect of the Diet and Physical Activity Program for Health, under the leadership of a nurse, on the dietary and physical activity behaviors of children. Methods: This study was planned in a quasi-experimental design with pretesting, posttesting, follow-up testing, and a control group. The study was conducted with 114 students in 2 schools. A total of 12 hours of training was given to the experimental group for 6 weeks. Institutional permission required for performing the study and an ethical consent from the commission for clinical trials of Marmara University institute of health sciences were received. Results: The results of the study reveal that Diet and Physical Activity Program for Health in posttest and follow-up periods was effective in improving dietary and physical activity behaviors of children within the program. However, the program's effect on dietary and physical activity self-efficacy was limited. Conclusion: The results of the study indicate that this program was effective in development of children's behavior regarding diet and physical activity.
Keywords: child; diet; physical activity; school nurse; OBESITY PREVENTION; ELEMENTARY-SCHOOL; INTERVENTION; CATCH; NUTRITION; STUDENTS